"I'm Demi and I Have Bipolar Disorder": Effect of Parasocial Contact on Reducing Stigma Toward People With Bipolar Disorder. Issue 3 (27th May 2017) - Wong, Norman C. H.; Lookadoo, Kathryn L.; Nisbett, Gwendelyn S.
Abstract : Examining celebrity influence, participants ( N = 594) completed an experiment to see if negative stereotypes toward bipolar disorder could be reduced as a function of mode of disease disclosure from a celebrity (Demi Lovato) diagnosed with the condition. Respondents were randomly assigned to view one of three conditions where the celebrity discusses her battle with bipolar disorder (or a comparison message). Measures assessing parasocial relationship (PSR), level of parasocial interaction (PSI), transportation, social distance towards, and negative stereotypes about people with bipolar disorder were used. Social distance and negative stereotypes toward people with bipolar disorder reduced significantly following exposure to Demi Lovato's disclosure about the disease via either TV/magazine interview. Implications of results for how celebrity disease disclosures may help reduce stigma toward bipolar condition are discussed.